Facile synthesis and the phase transition mechanism of fluoridated hydroxyapatite with a hierarchical architecture. Issue 48 (29th November 2017) - Wang, Liping; Wang, Ming; Wang, Yunli; Shao, Yiran; Zhu, Yingchun
Abstract : The crystal growth process of FHA is investigated. The crystal orientation relationship is found to be [010]FHA //[001]DCPA and (001)FHA //(010)DCPA . Abstract : Fluorine plays an important role in dental protection and formation of enamel materials, however the intrinsic effect of fluorine on the formation mechanism of fluoridated hydroxyapatite still needs to be known. In this work, pure fluoridated hydroxyapatite (FHA) with a hierarchical architecture was produced by a simple one-pot method using CaF2, Ca(OH)2 and Ca(H2 PO4 )2 ·H2 O. It was found that the hierarchical fluoridated hydroxyapatite showed a unique orientation structure and different phase transformation mechanism compared with hydroxyapatite (HA). In the phase transition process from DCPD (CaHPO4 ·2H2 O, brushite) to DCPA (CaHPO4, monetite), and then to FHA, hierarchical FHA was formed with the c -axis-oriented nanowires perpendicular to the planes of DCPA plates. More importantly, the crystal orientation relationship between FHA and DCPA was found for the first time to be FHA [010]//DCPA [001] and FHA (001)//DCPA (010), which is quite different from the crystal orientation relationship of HA [1̄10]//DCPA [110] and HA (1̄12)//DCPA (112). It was found that the phase transition process from (100)DCPA to (100)FHA was occurred with a good crystal lattice match. F − on (100)FHA had a small ionic radius and high electronegativity, decreased the crystal lattices of (100)FHA and might enhance their negativity and reactivity. This result may help better understand the effect of fluorine on the crystal growth process of natural enamel and the preparation of pure FHA with a hierarchical architecture is informative for the synthesis of enamel-like biomaterials.